Collaborative onscreen and offscreen play: examining meaning-making complexities - Lisa Kervin; Irina Verenikina; Maria Clara Rivera (Digital Culture & Education, 2015)
Playing with toys has been an established part of early childhood education for many years. Educators and theorists agree that opportunities to engage in make-believe play provide a wide range of avenues for enhancing literacy practices in the early years as children make meaning of their surrounding contexts. The increased availability and accessibility of mobile digital technologies has seen children more frequently engage in screen-based or “digital” play, sometimes leaving behind traditional forms of make-believe play with physical objects in physical spaces. However, when combined traditional make-believe and digital play complement each other in providing a rich texture for making meaning. An instance of onscreen and offscreen play is deconstructed to show the meaning-making complexities for child participants. This paper examines four propositions associated with meaning making – space, mediation, materiality and embodiment (Burnett, Merchant, Pahl & Rowsell, 2014) to discuss the complex and diverse relationships between the immaterial and material experience in a literacy episode which combines onscreen and offscreen play. Reported herein are the ways that imaginative play and literacy practices are enriched in the environments which blend physical toys and digital experiences.